2020
DOI: 10.1063/1.5142538
|View full text |Cite
|
Sign up to set email alerts
|

633-nm InGaN-based red LEDs grown on thick underlying GaN layers with reduced in-plane residual stress

Abstract: This work investigates the influence of residual stress on the performance of InGaN-based red light-emitting diodes (LEDs) by changing the thickness of the underlying n-GaN layers. The residual in-plane stress in the LED structure depends on the thickness of the underlying layer. Decreased residual in-plane stress resulting from the increased thickness of the underlying n-GaN layers improves the crystalline quality of the InGaN active region by allowing for a higher growth temperature. The electroluminescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 39 publications
1
126
5
Order By: Relevance
“…During MOVPE growth, carrier gases were N 2 , H 2 , or a mixture of the two. The schematic epitaxial structures of the InGaN-based amber and red LEDs have been reported in previous studies by our laboratory [14,15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During MOVPE growth, carrier gases were N 2 , H 2 , or a mixture of the two. The schematic epitaxial structures of the InGaN-based amber and red LEDs have been reported in previous studies by our laboratory [14,15].…”
Section: Methodsmentioning
confidence: 99%
“…We developed a novel high-temperature growth technique to grow high-quality and high-In-content InGaN layers, and demonstrated a long-wavelength electroluminescence (EL) peak emission of 740 nm [11,12]. Additionally, we adopted strain-compensation methods by introducing AlN/AlGaN barriers [13] and hybrid QWs [14,15] to reduce defects and enhance light output power. Also, we have demonstrated 665-nm InGaN-based red LEDs on β-Ga 2 O 3 substrates, allowing very low forward voltages below 2.5 V at 20 mA [16].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, with III-nitride technology blue LEDs are well developed and green LEDs are continuously being improved in efficiencies 36,37 . Obtaining efficient red-light emission is one of the main bottlenecks in III-nitride based RGB LEDs 38,39 . GaInP and AlGaInP alloys have been used in a wide range of optoelectronic applications involving efficient light emission or absorption in, e.g., solar cells 40 , window layers in solar cells 41 , LEDs 42 , and lasers 43 .…”
Section: Abbreviationsmentioning
confidence: 99%
“…For example, increasing the thickness and quality of the GaN buffer layer appears to be suitable for improving the performance of next-generation devices. [4][5][6] Hangleiter et al generated V-pits in an InGaN/GaN superlattice (SL) structure to release the strain in the InGaN active region; these V-pits, which originated from threading dislocations, also enhanced carrier injection, screening dislocations, and radiative recombination. [4,[7][8][9] Common approaches for improving the crystalline quality of InGaN active layers include the use of two-step high-temperature growth and hybrid structures.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Hangleiter et al generated V-pits in an InGaN/GaN superlattice (SL) structure to release the strain in the InGaN active region; these V-pits, which originated from threading dislocations, also enhanced carrier injection, screening dislocations, and radiative recombination. [4,[7][8][9] Common approaches for improving the crystalline quality of InGaN active layers include the use of two-step high-temperature growth and hybrid structures. Saito et al reported that twostep high-temperature growth, with different growth temperatures for the well and the barrier layer, improved the flatness of the barrier layer and maintained the uniformity of the thickness of the QW layer in the case of multilayer growth.…”
Section: Introductionmentioning
confidence: 99%